ECONOMIC FEASIBILITY ASSESSMENT OF BULLDOZER REPLACEMENT: A LIFE CYCLE COST ANALYSIS APPROACH - Asri, Shaumi Novila; Sudrajad, Oktova Yudha (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Coal mining operations are highly dependent on the reliability of heavy equipment to ensure the smooth flow of materials from production areas to delivery facilities. In the stockpile area of PT XYZ, bulldozers play a crucial role in coal dozing, spreading, and leveling activities that support supply to the Train Loading Station (TLS). High operating intensity and abrasive environmental conditions accelerate component wear, increasing the risk of performance degradation. Historical data indicate an upward trend in maintenance costs and bulldozer downtime frequency, which negatively affects cost efficiency and operational reliability. To date, PT XYZ does not have a structured quantitative policy to determine the optimal timing for heavy equipment replacement, resulting in largely reactive replacement decisions that may lead to cost overruns and disruptions to coal delivery schedules. This study aims to evaluate the economic feasibility of bulldozer replacement in the stockpile area of PT XYZ using a techno-economic approach. A deterministic case study method is applied using operational and maintenance data from 2019–2025, along with five-year cost projections. The analysis employs Life Cycle Cost Analysis (LCCA) and Equivalent Uniform Annual Cost (EUAC), with future cash flows discounted using the company’s Weighted Average Cost of Capital (WACC). The results show that although the existing unit exhibits declining annual capital costs, rising maintenance costs result in higher and more volatile total annual costs. In contrast, the new unit demonstrates lower and more stable EUAC, indicating that bulldozer replacement is the most economically efficient alternative.